Simplify 6a2 − 9ab + 2b2 − 3(ba − b2)
Answers
Answered by
4
Step-by-step explanation:
hey mate here is your answer
Attachments:
![](https://hi-static.z-dn.net/files/daf/f5cabacef700bfb48aed8366553f8ba2.jpg)
Answered by
1
The simplification of the given expression = 6
− 12ba + 5
Step-by-step explanation:
The given expression:
6 − 9ab + 2
− 3(ba −
)
To simplify the given expression.
∴ 6 − 9ab + 2
− 3(ba −
)
= 6 − 9ab + 2
− 3ba + 3
= 6 − 9ab − 3ba + 2
+ 3
= 6 − 12ba + 5
∴ The simplification of the given expression = 6 − 12ba + 5
Thus, the simplification of the given expression is equal to "6 − 12ba + 5
".
Similar questions